Professional Burnout of Faculty Members of Higher Educational Institutions - Kabanova, Elena E.; Vetrova, Ekaterina A.; Kubasova, Elena I. (International Journal of Criminology and Sociology, 2022)
The article is devoted to the analysis of professional burnout of the academic staff of a number of Moscow higher educational institutions. This problem most often affects residents of large cities, due to the intense rhythm of the city and lack of time for personal life, wasted on the way from home to work and back. The empirical basis of the study was the results of a sociological study conducted by the authors in 2019 on the basis of FSBEI HE Russian State Social University (RSSU), FSBEI HE Moscow State Humanitarian and Economic University (MSHEU), and FSBEI HE Russian State University of Tourism and Service (RSUTS). The problem of the deteriorated psychological state of teachers leading to professional burnout is poorly developed and causes increased research and practical interest, and gives rise to the practical need to improve the development of measures for the prevention and avoidance of burnout. All the above makes further research activity highly relevant, and may be extremely necessary in some universities. This is evidenced by the results of the study.: It is of vital importance to take measures to prevent professional burnout of the academic staff and to develop a strategy for a teacher-based approach considering personal qualities and potential. The administration should consider psychological, spiritual, and labor characteristics of teachers for the formation and distribution of individual schedules of teachers. The Novelty of the study is in investigating the professional burnout of the academic staff of an institution in Moscow.